6. The Effect of Celery Leaves Infusa (Apium graveolens L) on Reducing Level of Blood Glucose on Rat (Rattus norvegicus) Induced by Alloxan - Fatin Syarifahnur; Roslizawaty Roslizawaty; Amiruddin Amiruddin; Muhammad Hasan; T. Fadrial Karmil; Hamdani Budiman (Universitas Syiah Kuala, 2018)
This study aims to investigate the effect of celery leaf infusa on decreasing level of blood glucose in rat (Rattus norvegicus). Twenty five rats were divided into 5 groups namely first treatment group (P1) as negative control. Second treatment group (P2) as positive control, rats were induced with alloxan. Third treatment group (P3) rats were induced with alloxan and given 5% celery leaf infusa. Fourth treatment group (P4) rats were induced with alloxan and given 10% celery leaf infusa. Fifth treatment group (P5) rats were induced alloxan and given 15% celery leaf infusa for 14 days. The level of blood glucose of the rat was determined before treatment, after given aloksan and after given celery leaf infusa. Data were analyzed using Analysis of Varians (ANOVA). Results showed that administration of celery leaf infusa for 14 days, show significant effect to decreasing level of glucose in rat (P0.01). It can be concluded that the administration of celery leaf infusa concentrated 5%, 10% and 15% for 14 days show significant effect to decreased level of glucose in rats.